Peningkatkan Kemampuan Pemahaman dan Penalaran Matematis melalui Pendekatan Kontekstual - Rahmi Fuadi; Rahmah Johar; Said Munzir (Didaktik Matematika, 2016)
The low achievement on students mathematical comprehension and reasoning was still low due to the informational pattern of material in mathematics has been delivered to students informatively which means students get the information only from the teacher, so students mathematical ability also low. The purpose of this research was to examine the differences of comprehension ability and mathematical reasoning between students who learned mathematics through contextual learning and students who learned through conventional approach. Design for this research was pretest-posttest control group design. To obtain the research data, comprehension ability and mathematical reasoning test were used as the instrument. This research conducted at Madrasah Tsanawiyah Negeri Model Banda Aceh. The population of this study was all students at grade VIII while samples were chosen from 2 of 11 of grade VIII by purposive sampling. The data analysis was done quantitative way. Quantitative analysis conducted on the normalized average gain between two samples by using t-test. The result showed that overall learning mathematics by using contextual learning treatment can encourage students; comprehension ability and mathematical reasoning ability. Learning mathematics by contextual learning approach significantly better in encourage the students comprehension ability and mathematical reasoning than using conventional approach. Learning by contextual approach can be a good alternative learning approach that can be implemented in Junior High School